Analytical modelling of multi stage convergent supply chain system under just-in-time. (1st January 2011) - Jain, Deepak; Metri, Bhimaraya A.; Aggarwal, Vijay
The main objective of this paper is to develop an analytical model for operational level decisions for convergent supply chain system controlled by kanban under JIT where a product is assembled from a number of components supplied by many multistage supply chains. It integrates production and shipment lot size across the various stages of supply chain so that components travel through the supply chain in a coordinated way without any mismatch and final product reaches the customer in time. A quantitative analytical approach has been followed to develop the non-linear integer program (NLIP) and a generic LINGO program also has been developed for NLIP using branch and bound method for optimisation. This model facilitates integrated supply chain optimisation for system wide inventory, logistic and production setup costs optimisation. The model has been validated using automotive supply chain data. However, it can be applied to any industry.